PERAN LEMBAGA SOSIAL TERHADAP PEMBINAAN MORAL REMAJA DI SEKOLAH MENENGAH ATAS - Yunisca Nurmalisa; Muhammad Mona Adha (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
The purpose of The Role of Social Institutions Toward Moral Guidance Teeangers at SMA Se-Kabupaten Pesisir Barat research is to understand how the role of social institutions at SMA Se- Kabupaten Pesisir Barat in moral guidance teenagers. The method that is used in this research is qualitative descriptive with the subject of research are social institutions such as institute of family, institute of education, institute of religion, and institute of law. The data collecting technique was using interview guidance, observation, and documentation whereas the data analysis was using credibility experiment and triangulation. The result of this reasearch is showed that social institutions is comprehended and understood their duty as social institutions which is has assignment to make moral teenagers to be good. Based on the result, it can be concluded that social institutions such as institute of family, institute of education, institute of religion, and institute of law has a role but not yet maximal toward moral guidance teenagers